LINGUOPOETIC CHARACTERISTICS OF THE ARTISTIC TEXT AND INTERVIEW OF THE AUTHOR'S INDIVIDUAL STYLE - Ashurova, Zulhumor (FILOLOGIYA UFQLARI JURNALI, 2021)
This article discusses the linguopoetic features of the literary text, the author's individual style, peculiarities, as well as the ideological and thematic area reflected in the text, the set of dominant characters. The general and specific aspects of the artistic style are highlighted in the text.